Correlation and clinical significance of GSTP1 hypermethylation in hepatocellular carcinoma: a systematic review and meta-analysis - Li, Pengfei; He, Lei; Zhang, Chunxia; Huang, Xinyao; Sun, Rong; Zhang, Yan; Wang, Yan (Frontiers in Genetics, 2025)
BackgroundHepatocellular carcinoma (HCC) is one of the most prevalent and fatal cancers globally, with poor prognosis due to late-stage diagnosis and limited early detection methods. GSTP1 gene hypermethylation has been implicated in various cancers, including HCC, as a potential biomarker for diagnosis, prognosis, and therapeutic strategies. This systematic review and meta-analysis aimed to assess the association between GSTP1 hypermethylation and HCC, and its clinical significance.MethodsA comprehensive literature search was conducted across PubMed, Embase, Web of Science, and the Cochrane Library to identify studies examining GSTP1 hypermethylation in HCC. Studies included in the meta-analysis were observational (case-control, cohort) or experimental studies (clinical trials) that reported on the correlation between GSTP1 hypermethylation and clinical outcomes in HCC patients. Pooled odds ratios (ORs) and weighted mean differences (WMDs) were calculated using random or fixed-effects models based on heterogeneity.ResultsA total of 10 case-control studies were included, comprising 1,133 participants. The analysis revealed a significant association between GSTP1 hypermethylation and the presence of HCC (OR = 6.64, 95% CI: 2.17–20.38). GSTP1 hypermethylation was more frequently observed in liver cancer tissue compared to liver tissue from patients with other diseases (P < 0.00001). Additionally, a significant correlation between GSTP1 hypermethylation and poor clinical outcomes, such as advanced tumor stage, recurrence, and reduced overall survival, was observed (OR = 2.56, 95% CI: 1.80–3.64). Subgroup analyses based on study design, sample type, and detection method showed no significant heterogeneity in most comparisons.ConclusionGSTP1 hypermethylation is significantly associated with the presence of HCC and poorer clinical outcomes, making it a promising biomarker for early diagnosis and prognosis. These findings highlight the potential for GSTP1 methylation as a diagnostic and prognostic tool in HCC management. Further large-scale, multicenter studies are required to standardize detection methods and evaluate the therapeutic potential of epigenetic reactivation of GSTP1 in HCC patients.